Determining the properties of gas turbine engine components manufactured from VT6 titanium alloy powder (Ti-6Al-4V) by using additive electron beam technology - Matviichuk, Vladyslav; Nesterenkov, Vladimir (Eastern-European Journal of Enterprise Technologies, 2025)
This study considers components manufactured by additive electron beam manufacturing (EBM) from Ti-6Al-4V (VT6) titanium alloy powder. This material is one of the most widely used in aircraft engine production due to its combination of high weldability, strength, as well as resistance to fatigue loading. The task addressed is to achieve consistently high density, structural uniformity, and stable operational properties in gas turbine engines (GTEs) components manufactured from VT6 alloy by the EBM method. To fabricate specimens, a digital model was constructed in Materialise Magics, while layer-by-layer analysis and optimization of process parameters were carried out in Simufact Additive. Using the EBM process, experimental specimens were produced, including four GTE blades, a turbine wheel, and control samples. The chemical composition confirmed full compliance of the parts with the VT6 (Ti-6Al-4V) alloy standard. The microstructure is characterized by a lamellar α′-phase with a minor fraction of β-phase; the α-phase exhibits an acicular morphology with crystal thickness ranging from 0.5 to 1.5 μm. A uniform distribution of alloying elements, as well as the absence of segregation and porosity, was observed. The average microhardness value HV100 was determined to be 3.71 GPa. The results confirmed that the manufactured parts met the requirements for GTE components, demonstrating high density, strength, and operational reliability. The integration of simulation with subsequent EBM fabrication, optimization of process parameters, and the use of produced VT6 powder enabled the production of parts with zero porosity and stable microstructure. The components also showed controlled texture and high geometric accuracy. This confirms the effectiveness of the proposed approach and highlights its potential for scaling into serial production of critical components with predictable performance characteristics